Cultivation of microalgal Chlorella for biomass and lipid production using wastewater as nutrient resource. (May 2015) - Chiu, Sheng-Yi; Kao, Chien-Ya; Chen, Tsai-Yu; Chang, Yu-Bin; Kuo, Chiu-Mei; Lin, Chih-Sheng
Highlights: Agricultural wastewater shows a great potential for microalgal Chlorella growth. NH4 + -N in wastewater is the key factor for microalgal biomass and lipid production. Optimal N and P concentrations in wastewater for Chlorella cultivation were indicated. Limitations of microalgal biomass productivity by wastewater were detail discussed. Abstract: Using wastewater for microalgal cultures is beneficial for minimizing the use of freshwater, reducing the cost of nutrient addition, removing nitrogen and phosphorus from wastewater and producing microalgal biomass as bioresources for biofuel or high-value by-products. There are three main sources of wastewater, municipal (domestic), agricultural and industrial wastewater, which contain a variety of ingredients. Some components in the wastewater, such as nitrogen and phosphorus, are useful ingredients for microalgal cultures. In this review, the effects on the biomass and lipid production of microalgal Chlorella cultures using different kinds of wastewater were summarized. The use of the nutrients resource in wastewater for microalgal cultures was also reviewed. The effect of ammonium in wastewater on microalgal Chlorella growth was intensively discussed. In the end, limitations of wastewater-based of microalgal culture were commented in this review article.